2011
DOI: 10.1177/193229681100500402
|View full text |Cite
|
Sign up to set email alerts
|

Geoenvironmental Diabetology

Abstract: Abbreviations: (HbA1c) hemoglobin A1c, (NGO) nongovernmental organizationKeywords: air pollution, cold, diabetes, environment, heat, natural disasters AbstractMany reports have documented the negative health consequences that environmental stressors can have on patients with diabetes. Studies examining the interaction between the environment and a patient with diabetes can be unified under a single discipline termed "geoenvironmental diabetology." Geoenvironmental diabetology is defined more specifically as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 94 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…The complex interplay of factors has been reported to affect the level of physical activity amongst black and ethnic minorities in the UK [41]. The effect of changing environment due to migration was highlighted as influential in T2DM management process [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The complex interplay of factors has been reported to affect the level of physical activity amongst black and ethnic minorities in the UK [41]. The effect of changing environment due to migration was highlighted as influential in T2DM management process [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies which have found increased HbA1c levels of patients with diabetes following natural disasters. 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…Disasters are a phenomenon that may result in large-scale health impacts, including the worsened glycaemic control of patients with diabetes 18 19 and increased incidence of diabetes-related mortality for months postdisaster. 20 21 On 11 March 2011, Japan was hit by an earthquake, tsunami and nuclear disaster, referred to as the 3.11 triple disaster.…”
Section: Introductionmentioning
confidence: 99%
“…The outside temperature can also adversely affect people living with diabetes, with higher numbers of emergency department visits, hospitalisations and mortality during hot weather . In real life, people often store their medicines in areas exposed to extreme temperatures such as in a motor car during the summer.…”
Section: Planning For Physical Activity and Environmental Temperaturementioning
confidence: 99%